Analisis Literasi Keuangan, Sikap Keuangan, dan Pendapatan Terhadap Keputusan Investasi Mahasiswa Kota Batam - Sri Wati; Sunarto Wage (SEIKO : Journal of Management & Business, 2023)
Investment decisions of Batam City students occupy an important role in order to provide an alternative for obtaining money or profits in the future. This study used via a Likert scale, the sample was 375 students in Batam City. The data analysis method used was descriptive statistics, data quality test, classic assumption test, multiple linear regression test, determinant coefficient test, and hypothesis testing, then processed with the SPSS v26 program. The results of the study from the T test stated (1) financial literacy has a significant effect on investment decisions (2) financial attitude has a significant effect on investment decisions and (3) income has a significant effect on investment decisions. The results of the F test also say that financial literacy, financial attitudes, and income simultaneously have a significant effect on investment decisions. The results of the study of the coefficient of determination stated that the influence on investment decisions was 20.2% by the variables in this study, the remaining 79.8% was influenced by other variables that were not from this research variable. Kata Kunci: Financial Literacy; Financial Attitude; Income; Investment Decisions